Audit committee requirements in six major capital markets: How far have we come?. (February 2017) - Pandit, Ganesh; Conway, Grace; Baker, C.
Abstract This research discusses the key events that led to the establishment of the current regulations pertaining to the functioning of audit committees in six major capital markets of the world, namely, the U.S., U.K. Australia, India, South Africa, and Argentina, and also presents the findings based on a comparison of these regulations. Specifically, the authors review the changes that happened either proactively or sometimes as a reaction to certain events in each of these securities markets, leading to the current audit committee regulations. Also, the relevant local laws and requirements of the regulatory bodies along with the listing rules of the stock exchanges in the above six nations are examined to study how the requirements are both similar as well as different across the six continents. Given the increase in the number of multinational corporations selling shares in different capital markets where such entities have to conform to the regulations of each such market, a study of the audit committee regulations is expected to give some insight into how much rigor the different capital markets of the world have with respect to their expectations of the composition of the audit committee, what the committee's role should be, how it should conduct its business, and to whom it should report. The study shows that each of these six nations has had its share of corporate scandals and/or abuses of power by senior business executives that first caused losses for investors, and eventually led to the current regulations. In some of these markets, audit committee regulations advanced from being recommendatory and "principles-based" to being mandatory mainly because of the pressure from external stakeholders. The newer regulations in each securities market generally, though not always, represented improvement over the previous versions. The study also shows that today the audit committees of companies listed on the different stock exchanges being examined in this study are subject to similar or sometimes identical requirements in some respects. At the same time, there are other requirements where the authors see minor as well as noticeable differences. All in all, NYSE emerges as the stock exchange with the most rigorous expectations from the audit committee on various matters and especially with respect to the monitoring of the independent auditor. While the audit committee regulations in the developed world of the U.S., U.K., and Australia have set good examples of governance practices before the rest of the world, the securities markets in the emerging economies of India, South Africa, and Argentina are not far behind. There are areas where the regulations in India and South Africa actually demand more from their audit committees compared to those in the developed markets.